Development of Psychiatric Disorders after Mild Head Trauma according to Birth History - Oh, Ki Take; Cha, Byung Ho (Annals of child neurology, 2025)
Purpose: Mild head trauma in children has been associated with an increased risk of psychiatric disorders; however, the role of perinatal factors such as birth weight remains unclear. Children born large for gestational age (LGA) may have a higher risk for psychiatric disorders due to altered brain development. This study examined the relationship between birth weight and psychiatric outcomes following mild head trauma.Methods: We retrospectively reviewed pediatric patients (<18 years) who experienced mild head trauma (Glasgow Coma Scale scores 13–15) between January 1, 2013, and December 31, 2013. Psychiatric diagnoses were established by child psychiatrists according to Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria. Birth weight categories—small for gestational age, appropriate for gestational age, and LGA—were assessed for their impact on psychiatric outcomes using logistic regression analysis. Additionally, correlation analyses examined the relationship between birth weight and body weight at the time of trauma.Results: Among 178 patients, 18 (10.6%) developed psychiatric disorders, including posttraumatic stress disorder, attention-deficit/hyperactivity disorder, and adjustment disorder. Higher birth weight and LGA status were significantly associated with an increased risk of psychiatric disorders (birth weight: odds ratio [OR], 10.080; LGA: OR, 11.662; P<0.05). No significant correlation was identified between birth weight and body weight at the time of trauma (Pearson’s r=–0.091, P=0.206; Spearman’s rho=0.005, P=0.948).Conclusion: LGA status and higher birth weight may increase vulnerability to psychiatric disorders following mild head trauma. Further research incorporating genetic and neuroimaging factors is needed to enhance risk assessment and facilitate early intervention.